A CLINICAL STUDY IN THE MANAGEMENT OF AMAVATA (RHEUMATOID ARTHRITIS) THROUGH KSHARA VASTI ALONG WITH SHAMANOUSHADHI (International Journal of Ayurveda and Pharma Research, 2020)
Amavata is a disorder where in lot of similarity is seen with Rheumatoid arthritis. This is a systemic chronic inflammatory joint disorder which affect predominantly to synovial joints. Cardiac involvement, symmetrical involvement of joints along with pain, stiffness and swelling with number of systemic complications resembles the disease Amavata.Methods: A total of 15 patients considering inclusion and exclusion criteria were selected to study Amavata in detail according to Ayurvedic texts and Rheumatoid Arthritis of modern medicine. Kshara Vasti schedule followed by Shamanoushadhi Simhanada Guggulu 500mg twice and Rasna Saptak Kwatha 40ml as Anupana for 45 days was given for 38 days with 1 month follow-up period.Results: Out of 15, 11 patients (73%) falls under marked relief category, 3 patients (20%) falls under moderate relief category and lastly 1 patient (6%) falls under mild relief category in subjective parameters. In the objective parameters, 9 patients (60%), 11 patients (73.33%) falls under marked relief category of grip strength and tenderness respectively. 03 patients (20%), 2 patients (13.33%) falls under moderate relief category of grip strength and tenderness respectively. 03 patients (20%), 2 patients (13.33%), 14 patients (93.33%) falls under mild relief category of grip strength, tenderness and E.S.R respectively. 1 subject (6.66%) falls under no relief category of E.S.R.Conclusion: All parameters of assessment but Kshara Vasti showed better improvement in the symptoms of the disease Amavata.